Optical Thickness of Dielectric Layer in Solar Cell Design for Improved Efficiency: A Theoretical Insight - Francis Aungwa; Kehinde Ogunmoye; Igba D Solomon; Peverga R Jubu; Abah A Oche; Eli Danladi; Newton F Gesa; Adebayo T Adepoju; Emmanuel J Adoy; Michael B Ochang (Physics Access)
This study investigates the effect of varying dielectric layer thickness on the optical properties of solar cells using MATLAB. Dielectric layers with thickness ranging from 10 to 100 nm were analyzed across 200 to 1200 nm wavelengths. Results showed that absorption efficiency increased with thickness, reaching a peak at 100 nm, where the absorption value was approximately 0.9 at 600 nm. Reflectance stabilized around 0.45 to 0.50, while transmittance was minimized to about 0.05, indicating that almost all incident light was absorbed or reflected at this thickness. The highest efficiency recorded was 94.86%, confirming that the 100 nm dielectric layer provided the best balance between absorption and reflectance. These findings align with previous studies, which identified the 80–100 nm thickness range as optimal for enhancing solar cell performance. This research highlights the importance of precise thickness control in solar cell design to achieve maximum light absorption and device efficiency.